END OF THE UNIVERSE "A SCIENTIFIC PERSPECTIVE AND REALITY" - Hafiz Muhammad Azhar Usama; Dr. Attiq Amjad; Ameer Hamza; Muhammad Hammad Atta; Iram Salamat; Moazzam Nawaz Virk; Tanweer Khawar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research paper is to review the end of the universe and to explain the various aspects that have arisen as a result. The research style of this paper will be narrative. Despite his efforts, the future of the world has always been hidden from his eyes and the question has always been in his mind what will happen at the end of the world? This question is exactly like the questions asked about the beginning of the world, which could not be answered despite numerous assumptions, and everything that is before man about the beginning of the world is limited to the hypotheses and theories of scientists. There are those who under no circumstances can be given the status of certain knowledge. Our time is more astonishing than in the past. New space discoveries are forcing astronomers to reconsider their views on the origin of the universe. How will the universe and life begin and end?many scientists are concerned about the current state of the Earth and the crises it faces, and generally research the facts that could one day lead to the end of life and the extinction of the Blue Planet. The study of this research paper will be very helpful in understanding the causes and effects of the end of the universe.